Dynamic Supply Chain Capabilities: A Case Study in Oil and Gas Industry - Saad, Shatina; Mohamed Udin, Zulkifli; Hasnan, Norlena (International Journal of Supply Chain Management, 2014)
Supply chain (SC) is a dynamic process that entails a continuous flow of information, materials and funds across multiple functional areas, within and between chain members in order to meet customer’s requirements and to maximize their profit.  Such dynamic process requires instantaneous acquisition   and constant re-evaluation of partners, technologies and organizational structures.  However, firms may encounter problems related to the dynamic process. Petroleum companies, in this globalization era are one of the dynamic supply chain entities, which require dynamic processes of capabilities, due to their high degree of uncertainties.  Motivated by the complexity of uncertainty in the petroleum companies and its typical characteristic of SC, this study intends to understand the process of dynamic SC management.   Using the resource-based view and organizational learning theory as the basis for developing the framework of the study, this study aimed to identify and understand the process of dynamic SC capabilities.   Company in oil and gas in Malaysia will be chosen as the sample case in understanding the process of the dynamic SC capabilities and SC performance.   Due to the subjectivity of the study that requires understanding process of SC, this study proposes to employ interpretive paradigm where it would guide towards rigour qualitative methodology. This study will provide rich and thick description of the dynamic of SC where the outcome will contribute to the managerial and theoretical perspective of SC management in oil and gas industry.